High prevalence of overweight and obesity among 6-year-old children in Finnmark County, North Norway - Kokkvoll, Ane Sofie; Jeppesen, Elisabeth; Júlíusson, Pétur Benedikt; Flægstad, Trond; Njølstad, Inger (Acta Paediatrica, 2015)
This is the peer reviewed version of the following article: Kokkvoll, A., Jeppesen, E., Juliusson, P. B., Flægstad, T. and Njølstad, I. (2012), High prevalence of overweight and obesity among 6-year-old children in Finnmark County, North Norway. Acta Paediatrica, 101: 924–928, which has been published in final form at http://dx.doi.org/10.1111/j.1651-2227.2012.02735.x. This article may be used for non-commercial purposes in accordance With Wiley Terms and Conditions for self-archiving Aim: The aim was to determine the prevalence of overweight and obesity among 6-year-old children in Finnmark, the northernmost county of Norway. Methods: This is a survey of 1774 children born during 1999 and 2000 from 18 of 19 child healthcare centres in Finnmark. Body mass index data extracted retrospectively in 2007 from health records at the age of 6 years were compared with international definitions of over- and underweight. The prevalence figures were further compared with socio-demographic figures on municipality level. Results: Overall, 19% of the children were classified as overweight or obese; 5% were classified as obese. The prevalence of overweight and obesity was higher among girls (22%) than among boys (16%) (p < 0.01). The prevalence of underweight was 8% among both girls and boys. Despite large variations in the prevalence of overweight and obesity between municipalities (9–35%), no association was found with municipality figures on socio-demographic factors. Conclusion: In the northernmost county Finnmark, the prevalence of overweight including obesity among 6-year-old children was somewhat higher than in previous surveys from Norway, especially among girls. acceptedVersion